The development of online teaching materials and the evaluation of student achievement before and after learning: A sample case for Pharmacy undergraduates and a “Sterility Test of Pharmaceutical Products” lesson - Ruangsirikron , Ponnaak; Jinakul, Nanthawan (Burapha Journal of Medicine, 2023)
Abstract Introduction: The topic “Sterility testing of pharmaceutical products” is one of the essential lessons required for pharmacy students to learn and practice. Due to COVID-19 situation resulting in the use of online learning platforms, teaching materials related to this topic need to be produced and applied in the classroom including students’ self-study. Objectives: To produce, distribute and evaluate online teaching materials for undergraduate students at Mahidol University’s Faculty of Pharmacy, covering the topic of “sterility testing of pharmaceutical products.” Methods: Online teaching materials entitled “Sterility testing of pharmaceutical products using the membrane filtration technique’ was created and distributed to 128 3rd year undergraduate pharmacy students at the Faculty of Pharmacy at Mahidol University in Thailand. The materials were delivered via Microsoft’s MS-teams online teaching platform. 10 multiple-choice questions were given to each student pre and post learning periods to evaluate their achievements. The data from the questionnaires were analyzed and presented as mean, standard deviation, and percentage. The statistically significant difference between parameters was also calculated based on the p-value less than 0.05 (p<0.05). Results: : Outlines of our online teaching content included materials and equipment, including media preparations, growth promotion, suitability tests and how to conduct the assay in pharmaceutical products. The test scores between pre and post learning sessions were significantly different (4.25 ± 1.757 VS 8.64 ± 1.446, p<0.05). Conclusion: Online teaching materials can be used as a tool for learning management. An online platform can help students in terms of self-study and the improvement of their cognition. It also increases learner’s achievement levels, which may lead to the enhancement of other educational skills.